Cole is incorrect. The vertex form of a quadratic function is given by h(x) = a(x-h)^2 + k, where (h, k) represents the vertex of the parabola.
To rewrite the given quadratic function in vertex form, we need to complete the square. Here is the correct step-by-step process:
h(x) = x^2 -6x + 7
h(x) = (x^2 - 6x + 9) - 9 + 7
h(x) = (x-3)^2 - 2
Therefore, the correct vertex form of the quadratic function is h(x) = (x-3)^2 - 2. This means the correct vertex is (3, -2), not (3, 2) as Cole stated.
Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7
Cole said that the vertex is (3, 2). Is Cole correct? If not, identify the step in which Cole made the mistake and correct his work.
1 answer